'Stuck in the System': An Interpretative Phenomenological Analysis of Transmasculine Experiences of Gender Transition in the UK. (June 2023) - Mills, Tyler J.; Riddell, Kirstie E.; Price, Elizabeth; Smith, David R. R.
A gender dysphoria diagnosis is currently required in the UK to access NHS transition-related treatment. However, this approach has been criticised by academics and activists as pathologising, 'gatekeeping' transgender identities, and can be viewed by the transgender community as a barrier to necessary medical care. The present research examines transmasculine experiences of gender transition in the UK, focusing on exploring the barriers encountered during identity development and medical transition. Semi-structured interviews were conducted with three individuals, and nine individuals took part in a single focus group. The data were analysed using Interpretative Phenomenological Analysis producing three main themes: 'Conceptualising Stages of Transition'; 'NHS Communication and Support'; and 'Medicalisation, Power and Non-disclosure'. Participants conceptualised access to transition-related treatment as an intrusive and complicated process that negatively impacts identity development. They spoke of barriers such as lack of trans-specific healthcare knowledge, insufficient communication and support from healthcare professionals, and restricted autonomy arising from the pathologisation of trans identities. Results suggest transmasculine individuals may face numerous barriers when trying to access healthcare, and therefore, a move towards the Informed Consent Model could ameliorate many of these barriers and would empower service-users to make informed choices.